Widespread variation in salt tolerance within freshwater zooplankton species reduces the predictability of community‐level salt tolerance. Issue 1 (24th August 2022) - Arnott, Shelley E.; Fugère, Vincent; Symons, Celia C.; Melles, Stephanie J.; Beisner, Beatrix E.; Cañedo‐Argüelles, Miguel; Hébert, Marie‐Pier; Brentrup, Jennifer A.; Downing, Amy L.; Gray, Derek K.; Greco, Danielle; Hintz, William D.; et al.
Abstract: The salinization of freshwaters is a global threat to aquatic biodiversity. We quantified variation in chloride (Cl − ) tolerance of 19 freshwater zooplankton species in four countries to answer three questions: (1) How much variation in Cl − tolerance is present among populations? (2) What factors predict intraspecific variation in Cl − tolerance? (3) Must we account for intraspecific variation to accurately predict community Cl − tolerance? We conducted field mesocosm experiments at 16 sites and compiled acute LC50 s from published laboratory studies. We found high variation in LC50 s for Cl − tolerance in multiple species, which, in the experiment, was only explained by zooplankton community composition. Variation in species‐LC50 was high enough that at 45% of lakes, community response was not predictable based on species tolerances measured at other sites. This suggests that water quality guidelines should be based on multiple populations and communities to account for large intraspecific variation in Cl − tolerance.